Peculiarities of polyvascular disease and the diagnostic significance of the ankle-brachial index in patients with coronary artery disease: results from the real-world registry KAMMA (Clinical registry on patient population with polyvascular disease in the Russian Federation and Eurasian countries) - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; T. I. Batluk; N. A. Koziolova; A. I. Chesnikova; A. Y. Vaskin; D. S. Tokmin; I. G. Bakulin; O. L. Barbarash; N. U. Grigoryeva; I. V. Gubareva; et al. (Российский кардиологический журнал)
Aim. To investigate the prevalence and characteristics of polyvascular disease in the Eurasian region's population with one or more previously established locations of atherosclerotic arterial damage, and to evaluate the diagnostic importance of the ankle-brachial index (ABI) as a marker for polyvascular disease (PVD).Material and methods. A total of 1837 patients were included in the main branch of the KAMMA registry (patients with PVD), among which 91,6% had coronary artery disease (CAD) (n=1683). For further analysis, the group of patients with CAD was combined with 1222 patients included in the second branch of the registry — KAMMA-cardio, forming a patient population (n=2905), in which all patients had verified CAD. The mean age of patients was 66,0 [59,0; 72,0] years, with 60,3% being male. Peripheral arteries was assessed using ultrasound examination.Results. PVD was present in 95,6% of patients with coronary atherosclerosis: dual-region involvement was observed in 51,3% of patients, three-region involvement in 37,1%, four-region involvement in 3,4%, and five-region involvement in 2,0%. Stenoses of the common carotid artery were observed in 71% of patients, internal carotid artery — in 68%, lower limb artery — in 52%, and renal and mesenteric artery — in 8,3%. There were following diagnostic effectiveness of the ABI for detecting patients with lower limb artery stenosis was: sensitivity — 58,0%, specificity — 83,6%. The quality of antithrombotic and lipid-lowering therapy was insufficient.Conclusion. In the overwhelming majority (95,6%) of patients with CAD in the KAMMA registry, PVD was revealed, with nearly half of the patients having involvement in three or more arterial zones. In the patient population with CAD, there should be an active effort to identify patients with PVD, using at least the ABI determination and active modern antithrombotic and lipid-lowering therapy according to current clinical guidelines.